2021
DOI: 10.1016/j.ctro.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and feasibility of re-irradiation using carbon ions for pancreatic cancer that recurs after carbon-ion radiotherapy

Abstract: Background and purpose: Patients who receive carbon-ion radiotherapy (C-ion RT) for primary pancreatic cancer may experience locoregional recurrence; however, the treatment options for such patients are limited. We aimed to investigate the feasibility and efficacy of carbon-ion re-irradiation for patients with pancreatic cancer who experienced recurrence after initial C-ion RT. Materials and methods: Twenty-one patients with recurrent pancreatic cancer who underwent repeat Cion RT between December 2010 and Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Recently, several reports described re-irradiation for pancreatic cancer using C-ion radiotherapy [ 11 ], stereotactic body radiotherapy (SBRT) [ 12 , 13 , 14 , 15 ], and proton therapy [ 16 ]. Re-irradiation with C-ion radiation in 21 patients at a single center resulted in an LC rate of 53.5% and a 1-year survival rate of 48.7% [ 11 ]. Only one patient developed grade 3 acute toxicity and no grade 3 or higher late toxicities were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports described re-irradiation for pancreatic cancer using C-ion radiotherapy [ 11 ], stereotactic body radiotherapy (SBRT) [ 12 , 13 , 14 , 15 ], and proton therapy [ 16 ]. Re-irradiation with C-ion radiation in 21 patients at a single center resulted in an LC rate of 53.5% and a 1-year survival rate of 48.7% [ 11 ]. Only one patient developed grade 3 acute toxicity and no grade 3 or higher late toxicities were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another NIRS trial combined CIRT with concurrent gemcitabine, leading to 2-year overall survival rates of 35% in all patients and 48% in the high-dose group with stage III LAPC [ 74 ]. Encouraging results have also been reported from Gunma and Chiba with respect to C-ion reirradiation for the treatment of local recurrences [ 75 , 76 ]. A model of chemoradiotherapy for LAPC showed that Japanese results are superior to those reported in all trials conducted with X-rays in Europe and the USA in terms of TCP [ 77 ].…”
Section: Cirt For Hypoxic Tumors: Evidence Of Effectivenessmentioning
confidence: 99%
“… 1 Among the treatment options, carbon‐ion radiotherapy (CIRT) reportedly has shown some efficacy in unresectable and recurrent cases. 2 , 3 , 4 , 5 , 6 In CIRT for pancreatic cancer, the dose to the gastrointestinal (GI) tract surrounding the pancreas should be considered. In some cases, reducing the tumor dose is necessary to reduce the GI dose.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is one of the most intractable cancers 1 . Among the treatment options, carbon‐ion radiotherapy (CIRT) reportedly has shown some efficacy in unresectable and recurrent cases 2–6 . In CIRT for pancreatic cancer, the dose to the gastrointestinal (GI) tract surrounding the pancreas should be considered.…”
Section: Introductionmentioning
confidence: 99%